Parkinson's disease in intensive care unit: An observational study of frequencies, causes, and outcomes - Gunchan Paul; Birinder Singh Paul; Parshotum Lal Gautam; G Singh; S Kaushal (Annals of Indian Academy of Neurology, 2019)
Objective: To analyze the frequency, causes, and outcomes of admission to the Intensive Care Unit (ICU) among Parkinson's disease (PD) population so that preventive measures can be developed. Methods: We prospectively observed patients with diagnosis of PD admitted to ICU from January 2014 to December 2016. Based on etiology for hospital admission, they were divided into two groups – related to PD (further divided into direct or indirect) or not associated with PD at all. Etiology for hospitalization was determined from history and investigational data. The primary outcome was death or discharge from the hospital. Factors contributing to ICU admission were analyzed by comparing these patients with a cohort of 50 PD patients admitted to the neurology ward during the same study period. All values were expressed as mean (standard deviation) and percentages using SPSS version 16.0. Results: Fifty-three (36%) out of a total of 146 patients required ICU admission. Most common causes leading to admission in decreasing order of frequency were fever (34%), delirium (16%), falls (12%), encephalopathy (8%), gastrointestinal emergencies (6%); while direct disease-related severe dyskinesias were seen only in two patients (4%). 13.7% needed mechanical ventilation and mean duration of ventilation was 5.94 days with mortality rate of 20%. Significant factors predicting ICU admission, and thus, poor outcomes were age >65 years, history of previous admission within the last 12 months, delirium, and hypoalbuminemia. There was no significant association between the incidence of ICU admission and duration of disease or severity of the disease. Conclusions: Poor outcome in PD patients is due to systemic causes, hence multidisciplinary teamwork may improve outcome in these patients.